PENANAMAN NILAI DEMOKRASI MELALUI PEMBELAJARAN PPKN DI SMP - Giawa, Liusma (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
This research aims to determine the instillation of democratic values ​​through PPKn learning at Bintang Harapan Ulususua Private Middle School for the 2022/2023 academic year. Factors driving and inhibiting the implementation of democratic values ​​in classroom PPKn learning and efforts made to overcome factors inhibiting the implementation of democratic values ​​in PPKn learning at Bintang Harapan Ulususua Private Middle School for the 2022/2023 academic year. This type of research is descriptive type qualitative research. Data collection used interview and observation methods. In analyzing the data, researchers used the Miles & Huberman model of qualitative data analysis and checked the validity of the research data using triangulation techniques. Based on the results of research and discussion, it shows that democratic values ​​in PPKn learning at Bintang Harapan Ulususua Private Middle School have been implemented well so that democratic values ​​can be possessed by every student and can be applied in their daily lives. These democratic values ​​include: tolerance, freedom to express opinions, openness in communication, self-confidence, responsibility and cooperation. The driving and inhibiting factors for the implementation of democratic values ​​in Civics learning at Bintang Harapan Ulususua Private Middle School, the driving factors include: Exemplary teacher teachers, adequate facilities and infrastructure, providing motivation, namely awards in the form of added value to students who are active in activities. learning. Inhibiting factors include: a) Factors within students, b) Environmental influences, c) Lack of attention from parents. 3) Efforts made to overcome factors inhibiting the implementation of democratic values ​​in PPKn learning at Bintang Harapan Ulususua Private Middle School, include: a) Teachers providing understanding, b) Habituation of behavior, c) Reprimands, d) Awareness from parents, e) Communication effective.